Sosialisasi Dampak Bencana Hidrometeorologi Terhadap Keselamatan Jembatan Pada Siswa Siswi SMA 15 Padang - Etri Suhelmidawati; Veriza Agistin; Rangga Fernando; Ozzy Pratiwi; Micky Fetriani (LPPM POLITEKNIK LP3I, 2026)
Hydrometeorological disasters, including floods, tornadoes, and landslides, pose significant threats in Indonesia and can severely damage infrastructure, particularly bridges. A lack of public understanding, especially among students, regarding the effects of these disasters on infrastructure safety contributes to an increased risk of damage and casualties. This community service initiative seeks to improve the knowledge and awareness of students at SMA Negeri 15 Padang about the mitigation of hydrometeorological disasters and their implications for bridge safety. The educational materials, grounded in empirical data and disaster regulations, are presented in a format that is easily understandable through visual aids. The method used in this service is a qualitative descriptive approach by conducting field observations, interviews, and interactive discussions through socialization activities. The results of the activities show an increase in students' understanding of the types of hydrometeorological disasters, potential bridge damage, and mitigation steps that can be taken. In addition, students are also able to recognize warning signs on bridge infrastructure during disasters. Evaluation through questionnaires shows that interactive methods can strengthen students' understanding of disaster mitigation topics. Overall, this activity has successfully improved students' preparedness for hydrometeorological disasters.